Обучение русскому языку иностранных студентов-нефилологов на продвинутом этапе - Алексеенко, Т.Н.; Копылова, Е.В.; Тростинская, О.Н.; Корепанова, Т.Э.; Алексєєнко, Т.М.; Копилова, О.В.; Тростинська, О.М.; Корєпанова, Т.Е.; Alekseenko, T.M.; Kopylova, O.V.; Trostynska, O.M.; Corepanova, T.E. (Харківський національний університет імені В.Н. Каразіна, Центр міжнародної освіти, 2011)
В статье описаны основные направления и принципы обучения русскому языку иностранных студентов-нефилологов продвинутого этапа в Харьковском национальном университете имени В.Н. Каразина. Представлены учебные комплексы и пособия по русскому языку для иностранцев различных специальностей, разработанные на кафедре языковой подготовки ЦМО.
Навчання російської мови іноземних студентів-нефілологів на поглибленому етапі.
Training of the Russian Language for the Advanced Non-philological Foreign Students.
Main directions and principles of training the Russian language for the advanced non-philological foreign students at V.N. Karazin Kharkov National University have been described in the article. Russian text-books and educational complexes worked out at the department of the language preparation for the oreigners of different specialities have been presented.
Keywords: Russian as a foreign language; curriculum; non-philological students; educational complex; русский язык как иностранный; программа обучения; студенты-нефилологи; учебные комплексы; російська мова як іноземна; програма навчання; студенти-нефілологи; навчальні комплекси